Stomatopod Crustacea of the KUMEJIMA 2009 Expedition, Japan - Ahyong, Shane T. (Zootaxa, 2012)
The stomatopod Crustacea collected during the KUMEJIMA 2009 expedition to Kume Island, Ryukyu Islands, southernJapan, are reported. The collection comprises 20 species from three superfamilies, six families and 15 genera. Of these 20species, 10 are new records for Japan, of which one species, Gonodactylellus kume, is new to science. The new speciesranges from Japan to northern Australia and is most similar to G. micronesicus (Manning, 1971), differing in the colour ofthe meral spot of raptorial claw and shape of the pleopod 1 endopod of adult males. The identities of Alima angusta Dana,1852, and A. gracilis H. Milne Edwards, 1837, as junior synonyms of A. neptuni Linneaus, 1758, are fixed by neotype selection. A checklist of the 68 species of Stomatopoda recorded from Japan is provided.